Prediction of Youth Violence Perpetration by Parental Nurturing Over Time - Cheung, Chau Kiu Jacky (International journal of offender therapy and comparative criminology, 2025)
Parental nurturing, including maternal and paternal caring and discussing ethics, is likely to predict violence perpetration in the youth negatively. This prediction stands on social bond theory, which specifies that parents and their bonding are crucial to curb violence perpetration. Nevertheless, the prediction is unclear from adolescence to young adulthood. To clarify this, the present study examines the effects over 6 years, using the panel data of the National Longitudinal Study of Adolescent to Adult Health on 3,947 U.S. youths. The examination controlled for prior violence perpetration and, thus, its confounding factors. Results showed that paternal nurturing but not maternal nurturing at Wave 1 and Wave 2 consistently displayed statistically significant inverse effects on violence perpetration at Wave 3. However, the significant effects were very weak. Paternal nurturing was very weakly inversely predictive of youth violence perpetration 6 years later. This conclusion implies that promoting paternal nurturing is slightly but not tremendously helpful to prevent violence perpetration in youth later. Meanwhile, practice can capitalize on the features of paternal bonding to deploy male nurturing and role modeling for such prevention.